Effects of 4 weeks of foot exercise on subjective outcome and foot plantar pressure in elite adolescent dancers with hallux valgus: A pilot study - Liu, Z.; Zhong, Y.; Chen, S.; Tanaka, H.; Li, Y.; Katsutani, H.; Okunuki, T.; Yabiku, H.; Kumai, T. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Dancers have a higher prevalence of hallux valgus (HV) than the general population. However, no reports specifically addressing treatment strategies for HV in dancers, or their effectiveness have been published. This study aimed to determine the effects of 4 weeks of foot exercises on subjective clinical outcomes, the HV angle, and change of foot plantar pressure during specific dance techniques.